2001
DOI: 10.1248/bpb.24.409
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Dissolution of Tolbutamide by a Traditional Chinese Medicine, Sho-saiko-to (Xiao Chaihu Tang).

Abstract: Tolbutamide is classified into sulfonylureas prescribed for the treatment of diabetic patients. The sulfonylureas have a potent hypoglycemic effect and sometimes show delayed and erratic absorption, leading to unexpected hypoglycemia. [1][2][3] Simons et al. reported that absorption patterns of tolbutamide were well correlated to the dissolution rate from the tablet. 4) Although the rate of drug absorption is often not important in chronic therapy, some studies have suggested that the absorption kinetics of to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…16) Quantiˆcation of benzoic acid was also performed by the reported HPLC method. 17) Data analysis: Permeation rates of tolbutamide were calculated using the permeated amount of the drug a n da r ee x p r e s s e da sn m o l W min W cm 2 .…”
Section: Methodsmentioning
confidence: 99%
“…16) Quantiˆcation of benzoic acid was also performed by the reported HPLC method. 17) Data analysis: Permeation rates of tolbutamide were calculated using the permeated amount of the drug a n da r ee x p r e s s e da sn m o l W min W cm 2 .…”
Section: Methodsmentioning
confidence: 99%
“…The mixture that is also known as TJ-7 or Xiao Chaihu Tang is composed of seven herbals (Figure 9 ). It contains 17.5% root of Bupleurum falcatum (Bupleurum, Chai Hu, Saiko), 5.0% root/stolon of Glycyrrhiza uralensis (Licorice, Gan Cao, Kanzou), 7.5% root w/o rootlets of Panax ginseng (Asian ginseng, Ren Shen, Ninjin), 12.5% tuber w/o cork layer of Pinelliae ternatae (Pinellia, Ban Xia, Hange), 7.5% rot w/o periderm of Scutellaria baicalensis (Baical skullcap, Huang Qin, Ougan), 2.5% root/rhizome of Zingiber officinale (Ginger, Sheng Jiang, Shokyo), 7.5% fruit of Ziziphus jujube (Jujube, Da Zao, Daiso), and 40% additives (Nishimura et al, 2001 ; Wen, 2007 ). Each of these herbs contains several active biochemical constituents that are considered to predict their pharmacological effects.…”
Section: Herbal Supplementsmentioning
confidence: 99%
“…Therefore, to predict and prevent serious reactions induced by drug interaction, it is necessary to characterize the mechanism for increased absorption of tolbutamide after co‐administration with Sho‐saiko‐to. In previous studies, we have shown that Sho‐saiko‐to did not affect the gastric absorption of tolbutamide in rats [11] and that dissolution of tolbutamide was not changed by Sho‐saiko‐to [12] . Thus, we focused on the absorption processes of the drug in the small intestine.…”
Section: Introductionmentioning
confidence: 99%